THE EVOLUTION OF THEORETICAL APPROACHES OF THE CORPORATIONS’ ANALYSIS - Victor BAZILEVICH; Yuriy UMANTSIV (USV Annals of Economics and Public Administration, 2013)
The article explores the basis of methodology of the corporations' analysis. It is summarized the theoretical approaches to determine their economic substance. Characteristic features inherent in corporations are identified. It is stated that the study of the evolution of scientific views on the problem of the formation and development corporations in the world economic literature has revealed the most significant in terms of theoretical and methodological concept, updated the need for scientific development of the problem of formation of corporations in the economic system. Nowadays the scientists are united by a perception of corporations as a difficult economic institution, but there is no unity of opinion on its essential features. Thus, a holistic theory of corporations is at the stage of active formation.